The Marco Effect [compact disc, unabridged] : a Department Q novel - Adler-Olsen, Jussi (Adler-Olsen, Jussi. Department Q novel., 2014)
All fifteen-year-old Marco Jameson wants is to go to school like a normal kid. Revered as a god and feared as a devil, his uncle Zola forces the children of the clan to beg and steal. When Marco discovers a dead body, the work of Zola, he takes off. Carl Morck did not want his assistants to pick up a missing persons case. But when they learn that a mysterious teen named Marco has insight into the case, Carl is determined to solve the mystery and save the boy.